Length–weight relationships of Johnius coitor (Hamilton, 1822), Osteobrama cotio (Hamilton, 1822), and Gonialosa manmina (Hamilton, 1822), from the River Ganga, India. (19th September 2018) - Verma, Hari Om; Verma, Sushil Kumar; Mishra, Sandeep Kumar; Alam, Absar; Das, Shyamal Chandra Sukla; Thakur, Venkatesh; Kumar, Jeetendra; Jha, Dharma Nath; Srivastava, Rama Shankar; Das, Basant Kumar
Abstract: The relationship between length and weight of three fish species Johnius coitor (Family Sciaenidae), Osteobrama cotio (Family Cyprinidae) and Gonialosa manmina (Family Clupeidae) unknown to Fishbase were studied from the Allahabad waters of the river Ganga in India. Fishes were captured bi‐monthly from March 2017 to June 2018 using gill nets and cast nets of various mesh sizes. The b values determined from length‐weight relationships (LWRs) were 3.246, 3.373 and 3.024 for J. coitor, O. cotio and G. manmina, respectively.